2001
DOI: 10.1039/b105833a
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence quantification analysis of spatio-temporal chaotic transient in a closed unstirred Belousov–Zhabotinsky reaction

Abstract: We analyse the transient spatio-temporal chaos that we observe in the Belousov±Zhabotinsky reaction performed in a closed unstirred batch reactor by recurrence quanti®cation analysis (RQA). We characterize the chaotic transient by measuring the Lyapunov exponent and the Kaplan±Yorke dimension. The latter shows the fractality of the attractor. The importance of the coupling between hydrodynamics and kinetics for the onset of chaos is also shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In fact, as an excitable system, BZ reaction can support pulses, fronts and waves propagation, pacemakers and spirals being the most common structures observed. 10 Nevertheless, in recent years chaotic dynamics were detected when the BZ reaction was performed in unstirred spectrophotometric cuvettes, both in cerium 11,12 and ferroin 13 catalyzed systems. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, as an excitable system, BZ reaction can support pulses, fronts and waves propagation, pacemakers and spirals being the most common structures observed. 10 Nevertheless, in recent years chaotic dynamics were detected when the BZ reaction was performed in unstirred spectrophotometric cuvettes, both in cerium 11,12 and ferroin 13 catalyzed systems. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 Moreover, transient chaotic oscillations are observed in the BZ oscillating chemical reaction in a stirred batch reactor experimentally and numerically. [5][6][7][8][9][10] An unstirred closed BZ system during the normal chemical evolution before reaching equilibrium spontaneously shows the following sequence of dynamic behavior: period-1 f quasiperiodicity f chaos f quasiperiodicity f period-1. Two transition scenarios, that is, at the onset of chaos and at its end, are observed.…”
Section: Introductionmentioning
confidence: 99%
“…The length of the induction period decreases and the frequency of oscillations increases with increasing temperature [152,169]. It has recently been suggested that temperature may play an important part in the dynamics of the system [170]. The effect of temperature gradients on pattern formation is discussed in Section 5·6·3.…”
Section: ·7 the Effect Of Heat On The Bz Reactionmentioning
confidence: 99%